IMPLEMENTASI PROGRAM REHABILITASI SOSIAL DALAM PEMBERDAYAAN PENYANDANG DISABILITAS OLEH DINAS SOSIAL DAN PEMBERDAYAAN MASYARAKAT KOTA SAMARINDA - Riza Korin Alfarabbi; Kus Indarto (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problem: The implementation of the Social Rehabilitation Program for empowering people with disabilities is carried out by the Social and Community Empowerment Agency of Samarinda City. This program aims to provide a platform for people with disabilities by inspiring them, raising awareness of their talents, and encouraging their development. However, in the effort to empower people with disabilities, there are still some limitations, such as the uneven distribution of assistive devices like wheelchairs and canes. Additionally, there is a lack of outreach or socialization to the broader community to prevent discrimination against people with disabilities. Moreover, there are no facilities for independence training for people with disabilities, requiring them to be sent to other cities such as Surakarta, Cibinong, and Makassar for training, which is conducted only once a year.Purpose: This research was conducted with the aim of analyzing the implementation of the Social Rehabilitation Program in empowering people with disabilities by the Samarinda City Social and Community Empowerment Service and identifying inhibiting factors in the implementation of the Social Rehabilitation Program in empowering people with disabilities by the Samarinda City Social and Community Empowerment Service. Methodology: Research focus is based on Korten's theory, which consists of the compatibility between the program and the beneficiaries, the compatibility between the program and the implementing organization, the compatibility between the user group and the implementing organization, as well as the inhibiting factors in the implementation of the Social Rehabilitation Program in empowering people with disabilities by the Samarinda City Social and Community Empowerment Service. The type of research used is qualitative with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. The analysis used is an interactive model developed by Miles, Huberman, and Saldana.Results/Findings: research focuses on Korten's theory, which consists of the alignment between the program and its beneficiaries, the alignment between the program and the implementing organization, the alignment between the user groups and the implementing organization, as well as the factors hindering the implementation of the Social Rehabilitation Program in empowering people with disabilities by the Social and Community Empowerment Agency of Samarinda City. The type of research used is qualitative with a descriptive method. Data collection techniques include observation, interviews, and documentation. The analysis used is the interactive model developed by Miles, Huberman, and Saldana.Paper Type: Descriptive